EFEK SEDUHAN DAUN KELOR TERHADAP PERTUMBUHAN DAN PERKEMBANGAN ANAK TIKUS PUTIH JANTAN - Suaskara, Ida Bagus Made; Joni, Martin; Ariwati, Putu; Agus Sumardika, Putu; Gusman Maulana, Arofi (SIMBIOSIS, 2017)
ABSTRCT         Determine food intake growth as it relates to the energy content in food. Protein plays an important role in the process of body growth, production and reproduction. This study aims to determine the weight gain, the number of red blood cells (tbsp), and the weight of testis and epididymis as criteria for the growth and development of the pups after by steeping the leaves of Moringa. This study uses a randomized complete block design (RAK) and divided into 4 groups and each group consisted of 10 pups male rats, namely; the test group 0 (K0 / control)) given aquadem, the test group 1 (K1) is given steeping the leaves of Moringa with a dose of 50mg / kg, the test group 2 (K2) is given steeping the leaves of Moringa with a dose of 75 mg / kg, the test group 3 ( K3) Moringa leaves steeping given at a dose of 100 mg / kg. Data results of the weight, the number of red blood cells, and weight of testis and epididymis were analyzed by statistical LSD. The results of this study showed steeping the leaves of Moringa provided can improve the weight and the number of red blood cells (tbsp) mice, whereas the weight of testis and epididymis are not increased significantly p = 0.550. Keywords : moringa leaves, dose, weight, number of tablespoons, testis and epididymis
Keywords: moringa leaves, dose, weight, number of tablespoons, testis and epididymis